Comprehensive Interfacial Mechanisms of LiMnPO4-MWCNT Composite ratios in Acidic Aqueous Electrolyte. (1st November 2017) - Chiu, Tse-Ming; Barraza-Fierro, J.I.; Castaneda, H.
Highlights: Electrochemical characterization of LiMnPO4 composite in acidic aqueous electrolyte. Probabilistic/deterministic modeling for electrode microstructure quantification. Quantify kinetic parameters via geometrical guided transmission line modeling Abstract: A comprehensive electrochemical characterization was performed for different compositions of LiMnPO4 electrodes with additions of multi-walled carbon nanotubes (MWCNTs). Electrochemical testing based on DC and AC techniques helped to perform a quantitative analysis to corroborate the influence of the activation processes at the interface and the overall performance of the cathodes. The step-control process for the composite/electrolyte interface is influenced by the MWCNTs content at different bias potentials. The threshold saturation of MWCNTs was determined experimentally by materials characterization, electrochemical techniques, and theoretically by probability-deterministic transmission line modeling (TLM). TLM was coupled with the LiMnPO4 particle size distribution and the electrode microstructural variability to quantify interfacial mechanisms.